Development Of Pop Up Book Picture Story Book Media For Students In The Indonesian Language Subject In Grade III Of State Elementary School 02 Ameroro - Arna Juwairiyah; Shindi Shindi; Ahmad Ahmad (Journal of Humanities, Social Sciences, and Education, 2025)
This study aims to produce a product in the form of pop-up book-based learning media on Indonesian language subjects as a supporter of the learning process. The type of research used is R&D, namely research that develops a product. The development of a learning media uses the ADDIE learning system model consisting of: Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were 16 students of class III Negeri 02 Ameroro. Data collection techniques were carried out by validity testing and practicality testing. The results of the validity test study showed that the results of the material expert validator obtained a percentage of 93% by showing a very valid category, the media expert validator obtained a percentage of 91% by showing a very valid category, and the language expert validator obtained a percentage of 85% by showing a valid category. The assessment of the practicality of the media from the teacher obtained a presentation of 96% with a very practical category and the assessment of the effectiveness of the media through students obtained from the trial obtained a percentage of 81.4% with an effective category.